ADTU-05 Gut microbial composition in the migrant south-asian IBD population in UK. (8th June 2018) - Quraishi, Mohammed; Acharjee, Animesh; Bhala, Neeraj; Pathmakanthan, Shrikanth; Cooney, Rachel; Ghosh, Subrata; Gkoutos, Georgios; Beggs, Andrew; Rossiter, Amanda; Iqbal, Tariq
Abstract : Introduction: Epidemiological studies have highlighted that the South Asian migrant population in UK have a comparable risk of developing IBD but with a more aggressive phenotype than the white Caucasian population. It remains unclear if this is due to environmental/lifestyle factors or differences in host genetics. The human gut microbiota is impacted by health status and diet and therefore represents a potentially adaptive phenotype that is influenced by the environment. As the gut microbiota has been shown to be different in the native South Asian population compared to those in developed countries, we aimed to investigate if there were ethnic differences in the microbiota in IBD patients. Methods: Stool samples were collected from South Asian (n=20) and Caucasian patients (n=46) with IBD attending outpatient clinics at University Hospital Birmingham along with healthy controls (n=17). DNA was extracted and the V4 hyper-variable region of the 16S rRNA gene amplified and sequenced. Analysis was performed on the QIIME pipeline using the GreenGenes database. Diversity analysis was corrected for false discovery rates. Result: Patients with IBD had a significantly different gut microbial composition in comparison to healthy controls as expected (p=0.01). Gut microbial diversity was reduced in IBD (p=0.001). A significant decrease in Firmicutes phylum was observed in patients with IBD in comparison to healthy controls which was primarily due a reduced abundance of communities from genus Faecalibacterium praunitizii, Lachnospiracae, Ruminococcus and Blautia (p<0.002). Within the IBD cohort, the alpha or beta diversity of gut microbiota was very similar for South Asians and Caucasian patients. No significant differences were seen at any taxonomic levels. Published literature have previously demonstrated that the gut microbiota in healthy South Asians living in the subcontinent was enriched with populations of Lactobacillus, Ruminococcus, and Bifidobacterium bacteria. In our South Asian IBD cohort these microbial communities were significantly reduced. Conclusion: This is the first study to date investigating the gut microbial composition in the migrant population with IBD in UK. The gut microbiota in South Asian IBD patients is similar to Caucasian IBD patients living in UK. Our findings suggest the need to explore further the role environmental factors in the development of IBD associated dysbiosis but also the role of host factors in pathogenesis.